2016
DOI: 10.1007/s12035-016-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

MARK2/Par1b Insufficiency Attenuates DVL Gene Transcription via Histone Deacetylation in Lumbosacral Spina Bifida

Abstract: Dishevelled (DVL/Dvl) genes play roles in canonical and noncanonical Wnt signaling, both of which are essential in neural tube closing and are involved in balancing neural progenitor growth and differentiation, or neuroepithelial cell polarity, respectively. In mouse Dvl haploinsufficiency leads to neural tube defects (NTDs), which represent the second most common birth defects. However, DVL genes' genetic contributions in human NTDs are modest. We sought to explore the molecular impact on such genes in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…As described in our previous article(Chen et al., ), we performed high‐throughput sequencing of genomic DNA samples collected from subjects with NTD in the Han Chinese population ranging in age from gestational week (GW) 12 to 10 years old and from multiple local hospitals in six provinces in China. Ethnicity‐matched controls were collected from non‐medically related terminations and were free of any NTDs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in our previous article(Chen et al., ), we performed high‐throughput sequencing of genomic DNA samples collected from subjects with NTD in the Han Chinese population ranging in age from gestational week (GW) 12 to 10 years old and from multiple local hospitals in six provinces in China. Ethnicity‐matched controls were collected from non‐medically related terminations and were free of any NTDs.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to our previous article (Chen et al., ), target sequencing was performed on CYP26B1 (NC_000002.11; NM_019885.3; NP_063938.1); CYP26A1 (NC_000010.10; NM_000783.3; NP_000774.2); CRABP1 (NC_000015.9; NM_004378.2; NP_004369.1); ALDH1A2 (NC_000015.9; NM_003888.3; NP_003879.2); CRABP2 (NC_000001.10; NM_001878.3; NP_001869.1); RARA (NC_000017.10; NM_000964.3; NP_000955.1). Genomic DNA was prepared using a Truseq DNA Sample preparation kit (Illumina Inc., San Diego, CA), libraries constructed with Agilent Custom SureSelect Enrichment Kit, and run on an Agilent Custom enrichment array (Probe Code: BI426526171).…”
Section: Methodsmentioning
confidence: 99%
“…Morphogenesis and closure of the neural tube is affected by nutritional, environmental and genetic factors including Wnt/PCP signaling, which is illustrated by genetic association between NTD in humans and mutations in the PCP genes VANGL1, VANGL2, CELSR1, FZD6 , and DVL2 (Cai and Shi, 2014; reviewed in De Marco et al, 2014). Notably, also mutations in DVL1 or DVL3 have been identified in humans with NTD (Figure 2), although the correlation was not significant (De Marco et al, 2013; Merello et al, 2013; Chen et al, 2016). …”
Section: Dvl Paralogs In Vertebrate Embryonic Developmentmentioning
confidence: 99%
“…Mutations are indicated at the positions of amino acid changes. Changes detected in individuals with NTDs (De Marco et al, 2013; Merello et al, 2013; Chen et al, 2016) are color coded orange (predicted pathogenic) and gray (predicted benign, in all cases A>V). All ADRS mutations are (−1)-frameshift mutations resulting in altered amino acid sequences in the C-terminus and a premature stop (Bunn et al, 2015; White et al, 2015, 2016), which are indicated by hatched area and red line respectively.…”
Section: Dvl Paralogs In Vertebrate Embryonic Developmentmentioning
confidence: 99%
“…The etiology of NTDs is complicated and involves both genetic and environmental factors. Epidemiological studies have revealed that folate deficiency may increase the risk of NTDs in humans, and that folic acid (FA) supplementation during periconception can reduce this risk . Although the genetic causation of human NTDs is poorly understood, studies in more than 240 mutant mouse models of NTDs provide the basis for a plausible pathological mechanism.…”
Section: Introductionmentioning
confidence: 99%